Impact of a coating of pectin and Cinnamomum Zeylanicum essential oil on the postharvest quality of strawberries packaged under different modified atmosphere conditions - Yousra Zantar; Younes Noutfia; Amin Laglaoui; Amal Maurady; Mohamed Najib Alfeddy; Nadia El Abbassi; Mounir Hassani Zerrouk; Said Zantar (Discover Food)
Abstract Extending shelf life during storage and distribution has always represented a significant challenge in the value chain of strawberries and other perishable fruits. Thus, the combined effect of two Modified atmosphere packaging (MAP) techniques and pectin-based coating with Cinnamomum zeylanicum essential oil (CEO) was investigated on preservation of ‘Palmaritas’ variety. Strawberries were exposed to four treatments during 12 days of storage: Normal atmosphere without coating (control), normal atmosphere and a pectin-based coating with essential oil (NEC), modified atmosphere of 2.5% O2 + 15% CO2 + 82.5% N2, a pectin coating with essential oil (EC15CO2) and a modified atmosphere of 2.5% O2 + 20% CO2 + 77.5% N2, and a pectin coating with essential oil (EC20CO2). The studied parameters were weight loss, decay rate, firmness, color, total soluble solids (TSS), total phenolic content (TPC), total anthocyanin content (TAC), total flavonoid content (TFC), antioxidant capacity (AC), and phenolic and organic compounds. Results showed that a pectin-based coating with 0.17% Cinnamomum zeylanicum essential oil in a CO2-enriched atmosphere guaranteed significant preservation of several quality attributes of strawberries during storage at 6° C, especially firmness, color, TSS, TPC, TAC and TFC. Moreover, our total phenolic compounds measurement revealed an increase in gallic acid, trans-ferulic acid, kaempferol, and malvidin 3-O-glucoside, coupled with notably less degradation of caffeic acid, p-coumaric acid, and quercetin than in the control sample. Applying a CEO coating and storage in MAP effectively preserved organic acids, particularly oxalic acid and malic acid, while slowing down the degradation of vitamin C and citric acid. Thus, bioactive coating coupled with MAP presents a promising alternative for fruit storage, allowing a significant shelf-life extension while maintaining and stabilizing the principal quality attributes of strawberries.